Ecological situation in the modern Russian Federation: comparison with other countries as a basis for new ideas for the development of the state - M. S. Efremova (Управление)
Most of the existing environmental problems have not been resolved yet, and some of them become aggravated. There is awareness that the tools that have been used so far to solve these problems can’t handle them. There is an interest in the analysis of existing environmental problems among social activists. The purpose of this article is to develop new ideas and directions for improving the environmental policy of Russia, based on an analysis of existing problems. In work elements of comparative and systematic approaches and general scientific methods of analysis, synthesis, deduction and induction were used. The main environmental problems that exist in Russia are: waste management issues, water pollution, deforestation, skepticism towards alternative and green energy. The study revealed the need to consider new trends in the environmental policy of Russia from the standpoint of political ecology. Among the necessary measures, it is worth noting the following: the introduction of a new ideology that will put in the first place the harmonious relationship between nature and a human; introduction of environmental education; a new system of preparing the specialists, including courses on an environmentally oriented lifestyle; information policy, revealing the essence of existing environmental problems; support for environmental organizations; introduction of a new approach to alternative energy and green technologies.